Strengthening The Role Of Village Apparatus In Efforts To Achieve Village SDGs - Ni Nyoman Reni Suasih; Ni Putu Wiwin Setyari; Ida Ayu Nyoman Saskara; Ni Nyoman Yuliarmi; Anak Agung Istri Ngurah Marhaeni (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Village SDGs are an integrated effort to realize villages without poverty and hunger, economic villages grow evenly, villages care about health, villages care for the environment, villages care about education, women-friendly villages, networked villages, and cultural response villages to accelerate the achievement of Village SDGs. The village apparatus is a party that will facilitate the implementation of activities driven by the village government. This community services aims to improve the understanding of the Mas Village apparatus regarding the SDGs and Village SDGs, also to evaluate the data collection and implementation of village SDGs through counseling and FGDs. The results of the implementation of the activity show that it is still necessary to update the data on the indicators of the achievement of the Mas Village SDGs so that the acquisition of the Mas Village SDGs score can increase. In addition, the understanding of the Mas Village apparatus has increased so that in the future village development planning will be allocated for economic recovery programs, supporting national priority programs, and new adaptations in accordance with village authorities.